Produksi Karkas dan Koloni Escherichia coli dalam Usus Halus Broiler yang Diberikan Probiotik pada Waktu yang Berbeda - Muliani, Muliani; Wiryawan, Wiryawan; Pardi, Pardi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aimed to evaluate the effect of probiotic Bacillus spp. through drinking water on carcass production and the number of Escherichia coli colonies in the small intestine of broiler chickens. The research was conducted at the Applied Laboratory of the Faculty of Animal Husbandry, Mataram University, using 175 broiler chickens of the CP 707 strain randomly divided into five treatments and five replicates. The treatments consisted of one control (T1) without probiotics, and four treatments (T2-T5) with Bacillus spp. doses of 3 cc/liter of drinking water at different times. The design used was a completely randomized design (CRD), and data were analyzed using Duncan's test when there was a significant effect. The results showed that probiotic Bacillus spp. had a significant effect (P<0.05) on feed consumption and final body weight, but had no significant effect on carcass percentage or the number of Escherichia coli colonies in the small intestine. These findings indicate that probiotics can improve growth performance, but are not effective in significantly reducing the number of pathogenic bacteria.